2022
DOI: 10.2460/javma.22.05.0218
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of practice ownership among US private practice veterinarians extend to professional quality of life

Abstract: Objective To estimate the effects of practice ownership on wellbeing of US private practice veterinarians. Sample 1,217 practice owners and 1,414 associate veterinarians (ie, nonowners) who participated in the 2021 AVMA Census of Veterinarians and Practice Owners Survey. Procedures A professional quality of life instrument was used to measure compassion satisfaction (CS; a positive attribute), burnout (BO), and secondary traumatic stress (STS) in practice owners and nonowners both as scores and as score ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…In our study, practice owners showed lower total burnout scores than associate veterinarians. This is in agreement to prior veterinary studies in Germany ( 54 ) and the US ( 55 ). The characteristics of the practice owner role gives these veterinarians greater decision latitude and autonomy.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, practice owners showed lower total burnout scores than associate veterinarians. This is in agreement to prior veterinary studies in Germany ( 54 ) and the US ( 55 ). The characteristics of the practice owner role gives these veterinarians greater decision latitude and autonomy.…”
Section: Discussionsupporting
confidence: 93%
“…We believe it is crucial to improve the profession’s compassion satisfaction, and this can be facilitated through organizational efforts of each clinic [ 40 ]. Interestingly, while the literature suggested veterinarians often experience high secondary traumatic stress [ 2 , 4 , 12 , 13 ], our findings suggested none of our respondents have identified with high secondary traumatic stress. It is worthwhile to delve into the cause, as the outcomes from the current field of knowledge are incongruous.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous research suggested the complexity of veterinarians’ roles such as long working hours, heavy caseloads, engagement in euthanasia [ 1 , 7 , 8 ], the challenging nature of balancing clients’ expectations and medical interests [ 9 ], poor workplace culture [ 10 ], and isolated working conditions are predictors of veterinarians’ poor mental health status. Furthermore, studies have found that veterinarians with poor mental health are likely to experience burnout, higher levels of secondary traumatic stress, and lower compassion satisfaction [ 2 , 4 , 11 , 12 , 13 , 14 ]. Studies have also highlighted the easier access to pentobarbital [ 15 ], a drug commonly used for euthanasia of animals, to be a significant factor in their suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Associate veterinarians are twice as likely to develop feelings of reduced job satisfaction and are also more likely to experience burnout relative to practice owners (91,114). While both experience stress, veterinary practice owners exhibit far less burnout than non-owner associates (115). These findings are concerning as the rate of veterinary practice ownership has declined from 45% in 2013 to 36% in 2020 (114).…”
Section: Personal Demographicsmentioning
confidence: 99%